A Succinct review of strengths, weaknesses, opportunities, and threats (SWOT) analyses, challenges and prospects of solar and wind tree technologies for hybrid power generation - Mohanaravi, Kumaresen; Samykano, Mahendran; Pandey, Adarsh Kumar; Noor, Muhamad Mat; Kadirgama, Kumaran (Frontiers in Energy Research, 2024)
The increasing global demand for sustainable energy solutions has underscored the urgency of exploring renewable resources. Among these, sunlight stands out as a vast and essentially limitless source. This study examines innovative technologies including solar trees, wind trees, and hybrid solar-wind trees, which represent pioneering structures designed to harness renewable energy for diverse applications. Solar trees mimic natural foliage, featuring artificial structures adorned with solar modules to convert sunlight into electricity, offering promising prospects for sustainable urban landscapes. In contrast, wind trees are metallic arboreal forms housing micro-wind turbines and solar panels, exploiting both wind and solar energy, particularly suited for residential use. The integration of solar and wind technologies into hybrid trees ensures a consistent electricity supply day and night, throughout the year. These compact and cost-effective tree-shaped structures exemplify a new paradigm in renewable energy generation, promoting energy security, climate resilience, and economic prosperity. The review includes a comprehensive SWOT analysis, examining strengths, weaknesses, opportunities, and threats associated with solar, wind, and hybrid trees while considering sustainability aspects. This analysis provides foundational insights for renewable energy researchers, particularly those focused on hybrid wind and solar power systems, to develop optimal configurations. The review also discusses challenges such as land use requirements, aesthetic considerations, and public perception, offering recommendations for future research directions in this burgeoning field of sustainable energy technology.